Charting a path to more sustainable livestock value chains with a Rangelands Stewardship Council and a rangelands standard - Abiy, Rahel; Flintan, Fiona E. (International Livestock Research Institute, 2024)
Establishment of a global Rangelands Stewardship Council and rangelands standard